The absolute and relative risk of type 2 diabetes after gestational diabetes: A systematic review and meta-analysis of 129 studies - Dennison, Rebecca A (Diabetes Res Clin Pract, 2021)
AIMS: To estimate development of type 2 diabetes (T2DM) in women with previous gestational diabetes (GDM) and investigate characteristics associated with higher diagnoses, building on previous meta-analyses and exploring heterogeneity. METHODS: Systematic literature review of studies published up to October 2019. We included studies reporting progression to T2DM ≥6 months after pregnancy, if diagnostic methods were reported and ≥50 women with GDM participated. We conducted random-effects meta-analyses and meta-regression of absolute and relative T2DM risk. PROSPERO ID: CRD42017080299. RESULTS: In 129 included studies, the percentage diagnosed with T2DM was 12% (95% confidence interval 8–16%) higher for each additional year after pregnancy, with a third developing diabetes within 15 years. Development was 18% (5–34%) higher per unit BMI at follow-up, and 57% (39–70%) lower in White European populations compared to others (adjusted for ethnicity and follow-up). Women with GDM had a relative risk of T2DM of 8.3 (6.5–10.6). 17.0% (15.1–19.0%) developed T2DM overall, although heterogeneity between studies was substantial (I(2) 99.3%), and remained high after accounting for various study-level characteristics. CONCLUSIONS: Percentage developing T2DM after GDM is highly variable. These findings highlight the need for sustained follow-up after GDM through screening, and interventions to reduce modifiable risk factors.